﻿The surprising discovery of two new subterranean Leptodirini of the genus Spelaeobates Müller, 1901 (Coleoptera, Leiodidae, Cholevinae) from Croatia after more than a century - Srećko Ćurčić; Nikola Vesović; Maja Vrbica; Slađana Popović; Željko Radovanović; Nina B. Ćurčić; Anatoliy A. Yamashkin; Dejan Radović; Stanislav A. Yamashkin; Sofija Vranić; Tonći Rađa (Subterranean Biology, 2023)
Two new subterranean leiodid taxa of the genus Spelaeobates Müller, 1901 from three pits in northern Dalmatia (Croatia), S. coriniensis sp. nov. and S. coriniensis nonveilleri ssp. nov., are described. The morphological traits of the new taxa are enumerated and illustrated. These two taxa are placed in the subgenus Spelaeobates Müller, 1901. The relationships of these two taxa and their close relatives are clarified. Data on the sexual dimorphism of the two new taxa and on the intrasubspecific variability of S. coriniensis nonveilleri ssp. nov. are presented. We also redescribed S. novaki, the type species of both the genus Spelaeobates and the subgenus Spelaeobates and the closest relative of the newly described species. A key for identification of the taxa of the genus Spelaeobates is included. The new taxa are endemic to the Dinaric Alps of Croatia. Spelaeobates (Pretneriella) kraussi Müller, 1903 and S. (P.) pharensis langhofferi Müller, 1931 were found for the first time outside their type locality.